2007
DOI: 10.2193/2006-005
|View full text |Cite
|
Sign up to set email alerts
|

Extirpation Risk of an Isolated Black Bear Population Under Different Management Scenarios

Abstract: Habitat loss and anthropogenic mortality are recognized as threats to populations of large carnivores worldwide, yet their relative importance to extinction risk has rarely been quantified. We used population viability analysis (PVA) to estimate extinction probability of an isolated population of black bears (Ursus americanus) on the Bruce Peninsula, Ontario, Canada under different management scenarios. We used random‐effects analysis of variance to estimate components of variance in extinction risk explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 100 publications
(173 reference statements)
1
15
0
Order By: Relevance
“…We ran 1200 Monte Carlo simulations to estimate the geometric mean of λ using the life table-based Visual Basic program RISKMAN (Taylor et al, 2003; see also Dobey et al, 2005;McLoughlin et al, 2005;Wear et al, 2005;Clark and Eastridge, 2006;Howe et al, 2007), and estimated the standard error (SE) of λ numerically as the standard deviation (SD) of the generated values (Manly, 1997). One important feature of RISKMAN is that it is designed to accommodate the multi-annual (3-year) life cycle of polar bears.…”
Section: Population Rate Of Increasementioning
confidence: 99%
“…We ran 1200 Monte Carlo simulations to estimate the geometric mean of λ using the life table-based Visual Basic program RISKMAN (Taylor et al, 2003; see also Dobey et al, 2005;McLoughlin et al, 2005;Wear et al, 2005;Clark and Eastridge, 2006;Howe et al, 2007), and estimated the standard error (SE) of λ numerically as the standard deviation (SD) of the generated values (Manly, 1997). One important feature of RISKMAN is that it is designed to accommodate the multi-annual (3-year) life cycle of polar bears.…”
Section: Population Rate Of Increasementioning
confidence: 99%
“…Particularly for large predators park areas are often too small to support viable populations because park boundaries rarely coincide with ecological boundaries (Theberge et al, 2006;Patterson and Murray, 2008). Large predator populations are inextricably linked with the surrounding lands and consequently are faced with higher extirpation risk in case of increasing isolation (Newmark, 1995;Howe et al, 2007). Increasing conversion of habitats for human use may also limit management options inside protected areas .…”
Section: Introductionmentioning
confidence: 99%
“…Because adult female survival and recruitment appear to be the primary influences of bear population λ, we suggest these vital rates be monitored annually in this recolonizing population (Beston , Harris et al ). Given our relatively low estimated population Dtrueˆ, projected recolonization directions, and the limited connectivity with other populations in the region, we also suggest a conservative approach to annual harvests until the aforementioned vital rate estimates are acquired and a population viability analysis can be completed that evaluates the potential effects of harvest on λ and long‐term viability (Clark and Eastridge , Howe et al ).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Population monitoring studies have shown that even conservative harvest increases in small bear populations can cause precipitous population declines, and because of the relatively low reproductive rates inherent to bears, recovery from these reductions can be lengthy (Dobey et al , Howe et al , Clark et al ). Small populations are susceptible to heightened levels of demographic and environmental stochasticity compared to larger populations; they are already prone to increased probabilities of extinction and deleterious genetics effects without being subjected to exploitation (Lande , Mills ).…”
mentioning
confidence: 99%